K-Best Spanning Tree Dependency Parsing With Verb Valency Lexicon Reranking - Agić, Željko (Array, 2012)
A novel method for hybrid graph-based dependency parsing of natural language text is proposed. It is based on k-best maximum spanning tree dependency parsing and evaluation of the spanning trees by using a verb valency lexicon for a given language as a reranking knowledge base. The approach is compared with existing state-of-the- art transition-based and graph-based approaches to dependency parsing. As the proposed generic method was developed specifically for improving the accuracy of Croatian dependency parsing, Croatian Dependency Treebank and CROVALLEX verb valency lexicon are used in the experiment. The suggested approach scored approximately 77.21% LAS, outperforming the tested state-of-the-art approaches by at least 2.68% LAS.